2010
DOI: 10.3945/jn.110.123711
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Foods Fortified with Micronutrients Prevent Iron Deficiency and Anemia in Vietnamese infants ,

Abstract: To investigate whether an intervention including micronutrient-fortified complementary foods can improve iron status, we conducted a randomized controlled trial in 5-mo-old Vietnamese infants (n = 246). Villages (n = 29) were randomly divided into those receiving instant flour (FF) or a food complement (FC) both fortified with micronutrients or nothing [control (C)]. FF and FC infants received daily for 6 mo at least 2 meals of fortified complementary foods. Micronutrient status was assessed by measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In this survey material and procedure were controlled for contamination. The high prevalence of zinc deficiency in both women and children in this survey is intriguing, although consistent with several intervention trials carried-out in Vietnam in the recent years which indicated zinc deficiency prevalence ranging from 32% to 67% in young children under 2 years of age [14], [54] and of 52.1% among rural primary schoolchildren aged 6 to 8 years of age [8]. Moreover, according to a recent review assessing the risk of zinc deficiency, South and Southeast Asia, appear to be at the highest risk of zinc deficiency [59].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this survey material and procedure were controlled for contamination. The high prevalence of zinc deficiency in both women and children in this survey is intriguing, although consistent with several intervention trials carried-out in Vietnam in the recent years which indicated zinc deficiency prevalence ranging from 32% to 67% in young children under 2 years of age [14], [54] and of 52.1% among rural primary schoolchildren aged 6 to 8 years of age [8]. Moreover, according to a recent review assessing the risk of zinc deficiency, South and Southeast Asia, appear to be at the highest risk of zinc deficiency [59].…”
Section: Discussionsupporting
confidence: 90%
“…In this age group, the prevalence of anemia was considered as a moderate public health problem and most of anemia was associated with iron deficiency. More than half of children had ID, a finding consistent with intervention trials carried out in previous years in Vietnamese infants and young children [14], [53], [54]. In older children risk for anemia and ID was much lower, although still high for the 18–23 mo group (∼30%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of these, 121 [25-145] studies were on infants and children and 79 [146-224] were on women, while one study had both women and children as their study population [33] (Figure 2). Furthermore 125 [25-28,30,32-39,41-44,47,48,51,53],[54,56,59,60,62,63,65-73,75-77],[81-83,85,86,88-90,92,93,95-104,107-109],[111-117,119-127,129,130,132-136,139-144,223,225-228] of these trials were RCTs; the rest were quasi-experimental [46,55,61,74,78,87,91] and before-after studies [29,31,40,45,49,50,52,57],[58,79,80,84,94,95,105,131],[137,138,149,150,153,157,159-169,172],[174,177,181,183-186,189-191,193,195-…”
Section: Resultsmentioning
confidence: 99%
“…Food vehicles chosen varied for each micronutrient fortification and are described in detail in the relevant section. For the 125 RCTs included in this review, randomization and allocation concealment were adequate in 41 of the studies [33-37,56,60,63,65,68,69,72],[75,77,83,88,92,97,99,101],[103,107,108,112,113,115,116,122],[125,127,132,135,139,140,142,143],[146,147,188,214,217], information regarding attrition rates was adequately discussed with reasons in 110 studies [33-39,41-44,47,48,51,53,54,56],[59,60,62,63,65,67-73,75-77,81-83],[85,86,88-90,92,93,96-104,107-109,111-117],[119-127,129,130,132-136,139-144,171,173,175],[176,178-180,182,187,188,192,194,201],[…”
Section: Resultsmentioning
confidence: 99%